miR-22 exerts anti-alzheimic effects via the regulation of apoptosis of hippocampal neurons - Wang, Yu; Zhao, Lan; Kan, Bohong; Shi, Huiyan; Han, Jingxian (Cellular and Molecular Biology, 2018)
To investigate the expression of miR-22 in the hippocampus of amyloid Î² (1-42)-induced alzheimic rats, and to assess the underlying mechanism. A total of 60 male Sprague Dawley rats weighing between 274.65 and 293.97 g (mean weight = 284.31 ± 9.66 g) and aged 12 to 14 weeks were randomly assigned to three groups: control group (n = 20), Alzheimer's disease group (AD group; n = 20) and AD + miR-22 mimic group (ADMM group; n = 22). Rat AD model was established by injecting a solution of AÎ²1-42 into the hippocampal CA1 regions. After 24 h, rats in the ADMM group also received intraventricular injection of miR-22 mimic continuously for 28 days. The escape latency of rats, neuronal damage in the hippocampus, synaptic structure, brain-derived neurotrophic factor (BDNF), and the expressions of apoptosis-related proteins were assessed or determined, as appropriate. The expression of miR-22 in hippocampus of the AD group was significantly lower than that in the control group (p < 0.05). However, after 28 days of intraventricular injection of miR-22 mimic into AD rats, the expression was significantly increased, relative to control (p < 0.05). The escape latency of AD rats was significantly prolonged, and the number of platform sites significantly reduced when compared to the control group (p < 0.05). However, the escape latency was significantly shortened and the number of platform sites significantly increased in the ADMM group, relative to the control and AD groups. Results of transmission electron microscopy showed that the expression of miR-22 significantly reversed the degradation of synaptic structures in the hippocampus of AD rats as evidenced by recovery of abnormal synaptic cleft width and the length of synaptic active zones (p < 0.05). Results of Nissl staining revealed significant proliferation of gliacyte and loss of Nissl bodies. After miR-22 injection, the number of gliacytes in the hippocampus of AD rats was significantly reduced, while the number of Nissl bodies was significantly increased (p < 0.05). The expressions of BDNF in CA1 and CA2/3 regions of AD rats were significantly lower than those in the control group, and BDNF in the hippocampus of AD rats was significantly increased after 28 days of continuous injection of miR-22 (p < 0.05). The positive expression of Tunnel in the ADMM group (22.67 ± 2.96 %) was significantly higher than that in the AD group (4.49 ± 1.23 %), but significantly lower than that of control (39.51 ± 3.66 %) (p < 0.05). After 28 days of intraventricular injection of miR-22 mimic into AD rats, the expression of Bax protein was significantly down-regulated, while bcl-2 protein was significantly up-regulated (p < 0.05). The expression of miR-22 in the hippocampus of patients with AD inhibits neuronal apoptosis, thereby improving learning and memory dysfunction.